Model Predictive Control of Packed U Cells based Transformerless Single-Phase Dynamic Voltage Restorer - Trabelsi, Mohamed; Komurcugil, Hasan; Refaat, Shady S.; Abu-Rub, Haitham (IEEE, 2018)
Power quality has become a matter of great concern for all energy stakeholders, whether they are network operators, suppliers, producers, or end users. One of the main power quality issues affecting sensitive equipment and loads are short-time voltage variations (disturbances) called voltage sags and swells. This paper focuses on the mitigation of these voltage disturbances using a novel packed U cells (PUC) based dynamic voltage restorer (DVR) solution. The proposed DVR is controlled by using a multi-constraint model predictive control (MPC) approach, which regulates the injection of the needed compensation voltage in series and synchronism with the grid during the voltage disturbance events. Moreover, as it is mandatory to ensure stable operation of the PUC inverter, the proposed MPC ensures the control of the PUC output current while maintaining the capacitor voltage at its nominal value. Theoretical analysis and simulation results are given to show the high performance of the proposed solution.
19th IEEE International Conference on Industrial Technologies (ICIT) -- FEB 19-22, 2018 -- Lyon, FRANCE
Keywords: Packed U Cells Inverter; Dynamic Voltage Restorer; Model Predicitve Control; Voltage Compensation